The comparison between the nearest neighbor algorithm and the a-star algorithm to determine the optimal route for distributing napkin tissue - Riri Syafitri Lubis; Rima Aprilia; Ropiqoh Ropiqoh; Silvia Harleni (AXIOM : Jurnal Pendidikan dan Matematika, 2024)
Distribution is a factor that greatly influences the success of a company in selling its products. PT. Medan Jutarasa is a company that operates in the napkin tissue industry and has a Distribution Center (DC) to supply products to distributors. Distribution of products to consumers requires appropriate planning and consideration of which route to use to obtain more time-efficient transportation costs. In the delivery process, the company experienced problems, especially in the distribution route. The Nearest Neighbor algorithm searches for customers to serve based on the shortest distance from the vehicle's last location for further distribution. Meanwhile, the A-Star algorithm finds the shortest path using minimum cost. This research aims to compare the Nearest Neighbor algorithm and the A-Star algorithm to determine the optimal route for distributing tissue napkins by PT. Millionaire Medan. Based on the research results, it was found that the route using the Nearest Neighbor algorithm was more optimal than the A-Star algorithm in the distribution of tissue napkins by PT. Millionaire Medan.